A Survey on Antisemitism in Ontario's K-12 Schools - Robert Brym (Canadian Jewish Studies, 2025)
This study demonstrates the existence of a disjuncture between (1) the purported desire of Ontario schools to ensure that all students feel respected, included, and valued; and (2) the treatment of their Jewish students. Its main source of information is a survey of 599 Jewish parents and their reports on 781 antisemitic incidents in Ontario K–12 schools. Antisemitic incidents are defined as those that parents and their children consider antisemitic. The 781 incidents reported here were directly experienced by an estimated 10 percent of Ontario’s approximately thirty thousand Jewish school-age children. The survey was in the field from late January to early April 2025. It covers incidents that took place in the sixteen months (thirteen school months) from October 2023 to January 2025. The survey sample is roughly representative of the two-thirds of Ontario Jews most closely tied to the Jewish community by membership in synagogues or other Jewish organizations.